Conversational Implicature in “The Holdovers” Movie: Pragmatic Approach Directed by Alexander Payne - Ainiyah, Nur Rohmatul; Sholichah, Norma Ita (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The goals of this research to examine conversational implicature in